TAVR in Cancer Patients: Comprehensive Review, Meta-Analysis, and Meta-Regression - Marmagkiolis, Konstantinos; Monlezun, Dominique J.; Cilingiroglu, Mehmet; Grines, Cindy; Herrmann, Joerg; Toutouzas, Konstantinos Pavlos; Ates, Ismail; Iliescu, Cezar (Frontiers in Cardiovascular Medicine, 2021)
Objectives: This study sought to systematically analyze the available clinical evidence on TAVR therapy in cancer patients with symptomatic severe AS. Background: Aortic stenosis is the most common valvular heart disease in the world. TAVR has expanded the treatment options for this lethal disease process. The safety and efficacy of TAVR in cancer patients has not yet been reliably established. We thus conducted the largest known multi-center meta-analysis on TAVR and cancer status. Methods: We performed a literature search using PubMed, EMBASE, and Cochrane Central Register of Controlled Trials from January 2015 to January 2020. Studies that compared the use of TAVR in patients with severe symptomatic aortic stenosis and cancer against patients without cancer were included. Meta-regression was also conducted to determine if common clinical factors modified the possible association between cancer status and TAVR mortality. Results: Five studies with 11129 patients in the cancer group and 41706 patients in the control group met inclusion criteria. The short-term mortality in the cancer group was 2.4% compared with 3.3% in the control group (odds ratio: 0.72, 95% confidence interval: 0.63 to 0.82; p < 0.0001). The frequency of stroke was 2.4% compared with 2.7% (odds ratio of 0.87, 95% confidence interval: 0.76 to 0.99; p < 0.04). The frequency of AKI was 14.2% in cancer patients vs.16.4% (odds ratio of 0.81, 95% confidence interval: 0.76 to 0.85; p < 0.04). The rates of bleeding and need for new pacemaker implantation were not significantly different. Meta-regression demonstrated there was no significant association modifying. Conclusions: On the basis of the results of this meta-analysis TAVR appears may beas a safe and effective therapeutic option for patients with cancer and symptomatic severe aortic stenosis. Larger, longer, and randomized trials are required to adequately test this above hypothesis.